Modernising veterinary legislation for good governance : proceedings (OIE ParisFR, 2013)
Aims to address the concerns of OIE Member Countries wishing to strengthen the capacity of their national Veterinary Services and Aquatice Animal Health Services to deal with the challenges of today and the future while complying with OIE international guidelines and quality standards.
Keywords: ANIMAL HEALTH